A Large Animal Model of Right Ventricular Failure due to Chronic Thromboembolic Pulmonary Hypertension: A Focus on Function - Mulchrone, Ashley; Kellihan, Heidi B.; Forouzan, Omid; Hacker, Timothy A.; Bates, Melissa L.; Francois, Christopher J.; Chesler, Naomi C. (Frontiers in Cardiovascular Medicine, 2019)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a debilitating disease that progresses to right ventricular (RV) failure and death if left untreated. Little is known regarding the progression of RV failure in this disease, greatly limiting effective prognoses and therapeutic interventions. Large animal models enable the use of clinical techniques and technologies to assess progression and diagnose failure, but the existing large animal models of CTEPH have not been shown to replicate the functional consequences of the RV, i.e. RV failure. Here, we created a canine embolization model of CTEPH utilizing only microsphere injections, and we used a combination of right heart catheterization (RHC), echocardiography (echo), and magnetic resonance imaging (MRI) to quantify RV function. Over the course of several months, CTEPH led to a 6-fold increase in pulmonary vascular resistance (PVR) in four adult, male beagles. As evidenced by decreased cardiac index (0.12±0.01 v. 0.07±0.01 [L/(min*kg)]; p<0.05), ejection fraction (0.48±0.02 v. 0.31±0.02; p<0.05), and ventricular-vascular coupling ratio (0.95±0.09 v. 0.45±0.05; p<0.05), as well as decreased tricuspid annular plane systolic excursion (TAPSE) (1.37±0.06 v. 0.86±0.05 [cm]; p<0.05) and increased end-diastolic volume index (2.73±0.06 v. 2.98±0.02 [mL/kg]; p<0.05), the model caused RV failure. The ability of this large animal CTEPH model to replicate the hemodynamic consequences of the human disease suggests that it could be utilized for future studies to gain insight into the pathophysiology of CTEPH development, following further optimization.